Visible light-induced electronic structure modulation of Nb- and Ta-doped α-Fe2O3 nanorods for effective photoelectrochemical water splitting. (8th January 2018) - Chang, Han-Wei; Fu, Yanming; Lee, Wan-Yi; Lu, Ying-Rui; Huang, Yu-Cheng; Chen, Jeng-Lung; Chen, Chi-Liang; Chou, Wu Ching; Chen, Jin-Ming; Lee, Jyh-Fu; Shen, Shaohua; Dong, Chung-Li
Abstract: The photoelectrochemical (PEC) water splitting activity of Nb and Ta-doped hematite ( α -Fe2 O3 ) nanorods was investigated with reference to electronic structures by in situ synchrotron x-ray absorption spectroscopy (XAS). Current density-potential measurements demonstrate that the PEC activity of α -Fe2 O3 nanorods depends strongly on the species and concentrations of dopants. The doping of α -Fe2 O3 nanorods with a low level of Nb or Ta can improve their electrical conductivity and thereby facilitate charge transport and reduced electron–hole recombination therein. The photoconversion effects of Nb and Ta-doped α -Fe2 O3 by in situ XAS in the dark and under illumination revealed opposite evolutions of the spectral intensities of the Fe L-edge and Nb/Ta L-edge, indicating that charge transfer and a conduction pathway are involved in the photoconversion. Analytic in situ XAS results reveal that the α -Fe2 O3 that is doped with a low level of Nb has a greater photoconversion efficiency than that doped with Ta because Nb sites are more active than Ta sites in α -Fe2 O3 . The correlation between PEC activity and the electronic structure of Nb/Ta-doped α -Fe2 O3 is examined in detail using in situ XAS and helps to elucidate the mechanism of PEC water splitting in terms of the electronic structure.